2020
DOI: 10.1039/d0ra02501a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-ray crystal structure elucidation and Hirshfeld surface analysis of N-((4-(1H-benzo[d]imidazole-2-yl)phenyl)carbamothioyl)benzamide: investigations for elastase inhibition, antioxidant and DNA binding potentials for biological applications

Abstract: A new compound based upon a benzimidazole thiourea moiety that has unique properties related to elastase inhibition, antioxidant and DNA binding ability has been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…UV/visible spectroscopy is the easiest approach in which absorption intensity and peak shift variations in compound's spectra in DNA presence may help to identify binding via compound—DNA complex formation and further calculations of the binding parameters could determine the binding capacity of a compound. [ 16–21,42,43 ] While DNA viscosity measurement before and after the addition of a compound's concentrations may lead to substantial changes in DNA viscosity hence consider the most suitable and easy verification method to disclose reversible binding modes of interactions. If there is a rise in DNA viscosity with compound's concentrations, it means it gets intercalated between DNA base pairs [ 44 ] ; electrostatic/or groove binding interactions showed no significant change in DNA viscosity as less influence on DNA lengthening, [ 44 ] while consistency in the viscosity after some linear rise is an indication of mixed binding mode.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…UV/visible spectroscopy is the easiest approach in which absorption intensity and peak shift variations in compound's spectra in DNA presence may help to identify binding via compound—DNA complex formation and further calculations of the binding parameters could determine the binding capacity of a compound. [ 16–21,42,43 ] While DNA viscosity measurement before and after the addition of a compound's concentrations may lead to substantial changes in DNA viscosity hence consider the most suitable and easy verification method to disclose reversible binding modes of interactions. If there is a rise in DNA viscosity with compound's concentrations, it means it gets intercalated between DNA base pairs [ 44 ] ; electrostatic/or groove binding interactions showed no significant change in DNA viscosity as less influence on DNA lengthening, [ 44 ] while consistency in the viscosity after some linear rise is an indication of mixed binding mode.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19,46 ] The spectral changes indicated that compound 3 intercalated via partial/or complete insertion into DNA base pairs. [ 17,47 ] Intercalation feasibility could be accredited to planarity in the compound's structure and related to the overlapping of intercalating chromophore's electronic state (π * antibonding orbitals) and stacked DNA base pairs (π bonding orbitals). This overlapping causes π ‐ π * coupling that decreases transition probability hence resulted in hypochromism in the compound's spectra after the addition of DNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations